Epidemiological assessment of essential life skills and its determinants among adolescents in an urban slum area - Kritanjali Sahu Bose; Sujata Lavangare; Aritra Bose (Indian Journal of Community and Family Medicine)
Introduction: Life skills encompass a broad spectrum of psychological and interpersonal abilities essential for leading healthy and productive lives. This holistic approach, addressing knowledge, attitude, and skills, aims to modify behavior and foster balanced development. Life skills are crucial for supporting the mental health and competency of young individuals facing the challenges of adolescence – a transitional phase between childhood and adulthood. Material and Methods: This community-based cross-sectional study was conducted in a slum in Mumbai, where 158 adolescents (10–19 years) were selected by systematic random sampling. The sociodemographic profile and life skills were assessed among the study participants. The questionnaire for the measurement of life skills consisted of five domains: Time management, communication, leadership, goal setting, and coping skills. Results: Results revealed that skills of time management, goal setting, acquiring coping skills, and global life skills scores improved with the age significantly. Females exhibited better time management, which correlated with overall life skills. The literacy levels of parents influenced adolescents’ communication and leadership skills. Conclusions: Recognizing the nuanced influences on life skills development, interventions should address individual capacities and broader socioenvironmental factors. By fostering comprehensive life skills, interventions can contribute to the holistic well-being and positive development of adolescents facing diverse challenges in their transitional phase between childhood and adulthood.